2011
DOI: 10.1128/jcm.02642-10
|View full text |Cite|
|
Sign up to set email alerts
|

Multicenter Survey of Routine Determinations of Resistance of Helicobacter pylori to Antimicrobials over the Last 20 Years (1990 to 2009) in Belgium

Abstract: We analyzed the rates of antimicrobial resistance of Helicobacter pylori strains isolated from patients from 1990 to 2009 and identified risk factors associated with resistance. Gastric biopsy specimens were collected from several digestive disease centers in Brussels, Belgium. We routinely performed antimicrobial susceptibility testing for clarithromycin (CLR), metronidazole, amoxicillin, tetracycline, and ciprofloxacin. Evaluable susceptibility testing was obtained for 9,430 strains isolated from patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 49 publications
(78 reference statements)
6
36
0
Order By: Relevance
“…Primary clarithromycin resistance increased significantly, reaching peaks in 2000 for children (16.9%) and in 2003 for adults (23.7%). A subsequent decrease of the resistance rate down to 10% in both groups corresponded to a parallel decrease in macrolide consumption during the same period [13]. In accordance with this paper, Figure 2 shows a gradual increase in bacterial susceptibility in the course of the study period especially for clarithromycin.…”
Section: Discussionsupporting
confidence: 75%
“…Primary clarithromycin resistance increased significantly, reaching peaks in 2000 for children (16.9%) and in 2003 for adults (23.7%). A subsequent decrease of the resistance rate down to 10% in both groups corresponded to a parallel decrease in macrolide consumption during the same period [13]. In accordance with this paper, Figure 2 shows a gradual increase in bacterial susceptibility in the course of the study period especially for clarithromycin.…”
Section: Discussionsupporting
confidence: 75%
“…The primary resistance rate to CLA and to MET was even lower compared to the survey ten years ago . This decline was basically due to a reduced CLA resistance rate in some Western countries such as Belgium and France which successfully reduced the use of the newer macrolides . Otherwise the same risk factors for primary resistance could be identified in this small cohort as in the large European cohort sampled a decade ago in which living in Southern Europe was the strongest risk factor for resistance to CLA and coming from a migrant family a risk factor for resistance to MET.…”
Section: Discussionmentioning
confidence: 57%
“…Successful cure of the infection depends on the combination of drugs, their doses, the formulation, the duration of therapy, the adherence to therapy, and the strain susceptibility to antibiotics used in the regimen . The overuse of antibiotics in general and inappropriate or ineffective treatment regimens for H. pylori infections have led to a high proportion of strains with resistance to antibiotics such as clarithromycin, metronidazole, and levofloxacin used to treat this infection . Treatment regimens for first‐line therapy should provide a cure rate of at least 90%, preferably above 95% .…”
mentioning
confidence: 99%
“…A study in Belgium, where tetracycline resistance is rare, showed the female sex to be associated with H. pylori resistance to clarithromycin, metronidazole and ciprofloxacin (Miendje Deyi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%